Cooperating with Different Types of Strangers: The Influence of Guanxi Perception, Trust, and Responsibility - Haoxin Liu; Tulips Yiwen Wang; Allan B. I. Bernardo; Heyong Shen (Behavioral Sciences, 2023)
This study explored people’s estimation of cooperative intention when paired with people with different types of relationships, and the mediating roles of trust and responsibility between guanxi perception and the estimation of cooperative intention. We recruited 398 university students from the Greater Bay Area of China to complete two public goods dilemma experiments. Study 1 manipulated the type of partner to be either family member, classmate, and stranger, representing different types of guanxi. Study 2 manipulated the type of partner to be either stranger with intermediary, stranger within ingroup, and complete stranger. In both studies, the mediating roles of trust and responsibility in the relationship between guanxi perception and the estimation of cooperative intention were tested. The results of study 1 showed that the participants’ estimation of cooperative intention with a family member was higher than with acquaintances or with strangers. In study 2, the estimation of cooperative intention with stranger with intermediary was higher than with a stranger within one’s ingroup or with a complete stranger. Multivariate analysis verified the mediating effects. The results are discussed with reference to why Chinese people treat different types of guanxi distinctly, especially to different types of strangers, and how guanxi perception, trust, and responsibility work together to the influence of the estimation of cooperative intention.